Ergonomic Analysis Of A Developed Wheelchair Using Creative Algorithm - Ashiedu, F. I.; Okwu, M. O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
Mobility aids are important for disabled and aged patients for transportation or replacement for walking especially in indoor and outdoor environments. To guaranty the effective and efficient use of these mobility aids devoid of any form of epidemiological conditions, the level of comfort and ease of use must be ascertained. In this research, a simple and affordable wheel chair designed in previous work was analyzed to support patients in terms of ease and comfort of use. The method adopted for this study was the use of creative algorithm. Anthropometric measures were considered in the dimensioning of the wheel chair seat. It was necessary to test how ergonomically comfortable the wheelchair was in use by deploying an effective decision metrics tool known for dealing with complex decision-making process and may aid the decision maker to set priorities and make the best decision. By reducing complex decisions to a series of pair wise comparisons, and then synthesizing the results. Our findings showed an average ergonomic rating of 0.62 which indicate a relatively high degree of comfort ability in the use of the wheelchair. The use of these wheelchairs would greatly improve the community of people who have lost some means of independent mobility thereby leading to an improvement in their self-esteem. This will enable them pursues their daily vocation and life goals. The wheel chair will also serve as a novel for medical facilities in hospitals and help facilitate movement of disabled patients in homes, schools, entrepreneurial centres and hospitals.